2014
DOI: 10.3109/00016357.2014.954266
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of four denture adhesives on human gingival fibroblast cells

Abstract: The four denture adhesives evaluated in this study imparted cytotoxic effects on human gingival fibroblast cells. Staydent showed the highest toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…The MTT assay is a well-established method of determining cell viability and has been used in previous studies to test the cytotoxicity of dental adhesives and other dental materials because it is simple, fast, and objective (Costa et al, '99;Issa et al, 2004;Goldberg, 2008;Huang et al, 2010;Kusdemir et al, 2011;Khedmat et al, 2014;Lee et al, 2015). According to the MTT assay, the control group showed the highest odontoblast viability, followed by the SB, IB, XV, AO, CS, and EB groups.…”
Section: Discussionmentioning
confidence: 99%
“…The MTT assay is a well-established method of determining cell viability and has been used in previous studies to test the cytotoxicity of dental adhesives and other dental materials because it is simple, fast, and objective (Costa et al, '99;Issa et al, 2004;Goldberg, 2008;Huang et al, 2010;Kusdemir et al, 2011;Khedmat et al, 2014;Lee et al, 2015). According to the MTT assay, the control group showed the highest odontoblast viability, followed by the SB, IB, XV, AO, CS, and EB groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those who routinely swim or exercise sometimes utilize denture adhesives for support. Recent studies have revealed that continued use of denture adhesives with illfitting dentures increases vertical dimension, enhances alveolar bone resorption, and triggers hypersensitivity reactions, which has been shown to cause cytotoxicity effects on cultured cells in vitro [7][8][9] . In contrast, use of denture adhesives with correctly adapted dentures can improve retention and stability, increase bite force, and reduce the frequency of adjustments 10) .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, rapid improvements in biomechanical properties have recently been attained 12) , though additional information regarding the biocompatibility of denture adhesives is still needed 2,11,[13][14][15][16][17][18] . The cytotoxic effects of commercially available denture adhesives have been widely studied using agar diffusion and filter diffusion tests, as well as MTT assays with mono-layered cell culture systems 7,8,13,16,19,20) . As previously noted, denture adhesives are used not only for well-or ill-fitting dentures, but may also assist with retention, and have beneficial effects towards fibroblast and epithelial cells during healing, such as following a surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Em seguida, 100µL de solução solubilizadora de MTT (DMSO) foram adicionados a cada orifício da placa de cultura, que foi agitada levemente visando a dissolução dos cristais de formazan. Em seguida, a análise da atividade mitocondrial foi feita em espectrofotômetro com comprimento de onda de 500nm (LEE et al, 2015) (Figura 6A e B).…”
Section: Quantificação Das Célulasunclassified
“…Isso sugere que o tempo prolongado a exposição da prótese aos ciclos de imersão em clorexidina pode potencializar seu efeito antimicrobiano residual. HUANG et al, 2001;LEE et al, 2015;SONG et al, 2014). O teste do MTT também é considerado um método simples, rápido, objetivo e preciso (CHEN; WU; CHENG, 2014).…”
unclassified